2022
DOI: 10.3389/fphar.2022.959736
|View full text |Cite
|
Sign up to set email alerts
|

Pyrancoumarin derivative LP4C targeting of pyrimidine de novo synthesis pathway inhibits MRSA biofilm and virulence

Abstract: Staphylococcus aureus poses a serious public health threat because of its multidrug resistance and biofilm formation ability. Hence, developing novel anti-biofilm agents and finding targets are needed to mitigate the proliferation of drug-resistant pathogens. In our previous study, we showed that the pyrancoumarin derivative 2-amino-4-(2,6-dichlorophenyl)-3-cyano-5-oxo-4H, 5H- pyrano [3,2c] chromene (LP4C) can destroy the biofilm of methicillin-resistant S. aureus (MRSA) in vitro and in vivo. Here, we further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It is grouped in α-type (PSMα and PSMγ) and β-type (PSMβ) peptides ( 37 , 38 ). Research has shown that pyrancoumarin derivative LP4C effectively attenuates MRSA biofilm development by downregulating the expression of the genes psmα and psmβ ( 39 ). In this study, we found that the genes psmα and psmβ were also notably reduced after the treatment of S-342-3.…”
Section: Discussionmentioning
confidence: 99%
“…It is grouped in α-type (PSMα and PSMγ) and β-type (PSMβ) peptides ( 37 , 38 ). Research has shown that pyrancoumarin derivative LP4C effectively attenuates MRSA biofilm development by downregulating the expression of the genes psmα and psmβ ( 39 ). In this study, we found that the genes psmα and psmβ were also notably reduced after the treatment of S-342-3.…”
Section: Discussionmentioning
confidence: 99%
“…Our study developed the widely applicable and efficient PyrR-based CRISPR-Cas system in L. casei for whole genetic deletion, which provided novel insights into the molecular mechanisms of the PyrR gene in relation to the antimicrobial antagonism of metabolic products, competition with pathogens for adhesion, and immunoregulation. The molecular docking results indicated that the pyrR protein attenuates the virulence of biofilm formation and targets the de novo pyrimidine synthesis pathway in S. aureus [14]. To increase the sensitivity of 5-FOA, the double-mutant strain ∆pyrF ∆pyrR in Geobacillus kaustophilus was constructed.…”
Section: Discussionmentioning
confidence: 99%
“…Coumarins are important phenolic substances and exhibit the broad-spectrum anti-biofilm activity against a wide range of bacteria [ 21 , 22 , 23 ]. Our previous results showed that coumarin derivative LP4C was the potential anti-bacterial biofilm compound in vitro and in vivo [ 18 , 19 ]. The present study further confirmed that LP4C inhibited bacterial biofilm formation even at 5 μg/mL, which was about 80 times lower than the other reported coumarin derivatives, such as esculetin (6,7-dihydroxycoumarin) and esculin [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that 4-hydroxycoumarin derivate DCH could inhibit the biofilm formation of methicillin-resistant Staphylococcus aureus (MRSA) selectively [ 17 ]. Interestingly, we screened another coumarin derivate LP4C which exhibited significant inhibitory activity to biofilm formation in S. aureus and P. aeruginosa [ 18 , 19 ]. These results highlight the potential role of coumarin derivatives as new therapeutic agents to combat the bacterial biofilm infection.…”
Section: Introductionmentioning
confidence: 99%